2002
DOI: 10.1016/s0017-9310(02)00056-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of flash evaporation of a water film

Abstract: Je tiens tout d'abord à remercier Monsieur Bernard DESMET, Professeur à l'université de Valenciennes et Directeur du Laboratoire de Mécanique et d'Énergétique de Valenciennes, pour m'avoir accueilli dans son laboratoire ainsi que pour les discussions que 1' on a pu avoir. J'adresse également mes plus vifs remerciements à Madame Monique LALLEMAND, et Monsieur Prabodh K. PANDA Y, Professeurs des universités, pour avoir accepté de juger ce travail, et de participer au jury. Merci aussi à Monsieur Patrick FIN, Dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 12 publications
(19 reference statements)
2
54
0
Order By: Relevance
“…Volumetric heat transfer coefficient 3.3.1. Volumetric heat transfer coefficient evolution during flash Considering that the boiling during flash takes place in the whole bulk of waterfilm rather than on the steam-liquid interface, volumetric heat transfer coefficient is firstly proposed in our former work [11] to measure the intensity of boiling heat transfer for flash [7,11]. Thus, Eq.…”
Section: Non-equilibrium Fraction (Nef)mentioning
confidence: 99%
See 1 more Smart Citation
“…Volumetric heat transfer coefficient 3.3.1. Volumetric heat transfer coefficient evolution during flash Considering that the boiling during flash takes place in the whole bulk of waterfilm rather than on the steam-liquid interface, volumetric heat transfer coefficient is firstly proposed in our former work [11] to measure the intensity of boiling heat transfer for flash [7,11]. Thus, Eq.…”
Section: Non-equilibrium Fraction (Nef)mentioning
confidence: 99%
“…Besides, Miyatake et al also investigated the influence of waterfilm concentration on the bubble growth in stable pool boiling, and set up a simple calculation model [5,6]. Saury et al [7] also carried out static flash experiments with pure water as working fluid, but enlarged the range of superheats to between 1 and 35 K. Results suggested that the sensible heat released from the temperature drop of waterfilm could be considered to all change into the latent heat of generated steam. Saury et al further examined the influences of waterfilm height and depressurization rate on NEF elevation and evaporated mass [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the water is not significantly heated over the ambient temperature, and vaporization results from superheat of the liquid due to the low pressure, i.e. due to ambient pressure being lower than the saturation pressure at the given temperature of the saline water droplet, the evaporation can be considered to be driven by the pressure difference between the saturation pressure Psa, at the surface temperature of the droplet and the ambient low pressure P~ [7] The main contributing factor for the variation of droplet temperature with time in Eq. (2) is the evaporation at the surface.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…When the temperature difference between the liquid and the saturation temperature (which corresponds to the external vapor pressure) becomes significant, vapor bubbles form in the bulk of the liquid and rapidly move to the surface resulting in flash evaporation. This phenomenon is associated with a significant drop in the temperature of the liquid from the latent lent of the vaporization [7] and the vaporization ceases the moment the liquid is sub-cooled below the saturation temperature. The liquid has a very heterogeneous temperature distribution with superheat, saturated and sub-cool zones when flash evaporation occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars have investigated the flash evaporization process of water bulk from high pressure environment to vacuum. Saury et al [22] experimentally studied the flash evaporation of a water film with initial equilibrium temperatures from 30 to 75°C, and pressure varying between 5 and 20 kPa. They identified the parameters which influenced the flash evaporation: the initial temperature of liquid and superheat.…”
Section: Introductionmentioning
confidence: 99%